Human adaptation and diversification in the Microsporum canis complex - Xin Zhou; Sarah A. Ahmed; Chao Tang; Maria Eduarda Grisolia; José Francisco Ghignatti Warth; Kristen Webster; Andrea Peano; Silke Uhrlass; Claudia Cafarchia; Marie Pierre Hayette; Rosalie Sacheli; Tadeja Matos; et al. (IMA Fungus, 2023)
Abstract The Microsporum canis complex consists of one zoophilic species, M. canis, and two anthropophilic species, M. audouinii and M. ferrugineum. These species are the most widespread zoonotic pathogens causing dermatophytosis in cats and humans worldwide. To clarify the evolutionary relationship between the three species and explore the potential host shift process, this study used phylogenetic analysis, population structure analysis, multispecies coalescent analyses, determination of MAT idiomorph distribution, sexual crosses, and macromorphology and physicochemical features to address the above questions. The complex of Microsporum canis, M. audouinii and M. ferrugineum comprises 12 genotypes. MAT1-1 was present only in M. canis, while the anthropophilic entities contained MAT1-2. The pseudocleistothecia were yielded by the mating behaviour of M. canis and M. audouinii. Growth rates and lipase, keratinolysis and urea hydrolytic capacities of zoophilic M. canis isolates were all higher than those of anthropophilic strains; DNase activity of M. ferrugineum exceeded that of M. canis. The optimum growth temperature was 28 °C, but 22 °C favoured the development of macroconidia. Molecular data, physicochemical properties and phenotypes suggest the adaptation of zoophilic M. canis to anthropophilic M. ferrugineum, with M. audouinii in an intermediate position.